Vegetative Multiplication of Superior Phenotypes and Clone Bank Establishment in Casuarina equisetifolia - Balasubramanian, A.; Gurumurthi, K. (Indian Journal of Agroforestry, 2020)
The clonal selection in the seed raised base population was carried out in the coastal area of Tamil Nadu. The selection was resorted by employing the selection index method and about 52 candidate plus trees (CPTs) were selected. The selected CPTs were vegetatively propagated in the form of clad odes. The clad ode cuttings were collected in the morning from the mother trees and were placed inpre-soaked ’Jalsakthi’ (Jalsakthi is a synthetic biodegradable material, capable of holding water to 100 times to its weight). The well hardened propagated propagules of all the 52 clones were planted in the clonal garden of the Institute of Forest Genetics and Tree Breeding, Coimbatore in a completely randomised block design (CRBD) with three replications. All the clones were planted in 1 m x 1 m spacing and all the growth characters were recorded at 3 months interval for clonal evaluation and clone bank establishment. Almost all CPTs selected were rooted within 15 days. The rooting percentage of the clones varied from 6 (TCR-12-02-04) to 95.33 (TCR-02-01-01). The average rooting potential of the clones was 57.06 %. The potential of clones to with stand the transplanting shock (root trainer to polybag) varied from 26.33 % (TCR-02-01-02) to 96 % (TCR-11-01-01). The average survival potential of the cloneswas 70.52 %.The fully developed ramets of the clones were carefully transferred from poly bag to field and the clones wereraised in CRBD design for evaluation. The meansurvival of clones in the field was 96.85%. This technique can be used for vegetative propagation of CPTs of C.equsetifolia.